Challenges of Work-Life Balance Faced by Working Fathers in Kathmandu Valley: Evidence from Cross-sectional Data - Niranjan Devkota; Rocky Mani Shakya; Seeprata Parajuli; Udaya Raj Paudel (International Journal of Marketing & Human Resource Research, 2022)
Work-life balance has been considered as important component in individual life. Today in order to attract and retain their employees organizations are considering work-life balance as their prime concern. The main purpose of this study is to examine the work-life balance of working fathers in Kathmandu Valley. This study followed descriptive method of data analysis and 405 samples were collected with the help of non-probability sampling method. Further, the study revealed that satisfaction and motivation are considered to be key factors that help to maintain work-life balance. However unhelpful attitude of colleagues is found to be major reason creating work-life unbalance. 77.03% working fathers stated that they face challenge in maintaining work-life balance. This, it is recommended that by maintaining structural consistency in the workplace challenges of work-life can be mitigated up to certain extent. These findings will have implication at organizational level. The study concluded that high level stress, unsupportive relationships, unrealistic demands, unhelpful attitude and lack of control were found to be major challenges for maintaining work-life balance.